Production and manipulation of two dimensional droplet aggregates - Barkley, Solomon (My University, 2015)
This is a `sandwich thesis' comprising three distinct research streams I have pursued during the course of my master's degree. The first two streams have concluded, each resulting in a manuscript that is presented as a separate chapter of this thesis. The third research stream is ongoing, but preliminary results are presented in another chapter of this thesis. The first research stream presented in this thesis concerns the development of a technique to produce droplets with diameters as small as 5 microns with an extremely narrow size distribution in comparison to other methods. Other advantages of this technique, known as he snap-offf method, include its simplicity and ease of tuning droplet size. The results of this research are presented in chapter 3 in the form of a manuscript that is currently in press. The second research stream of this thesis explores the physics that drive droplet snap-off. A model was developed to predict the size of droplets, dependent on fluid properties, system geometry, and fluid flow rate. Experiments examined each of these parameters in turn, providing a cohesive understanding of the mechanism behind droplet snap-off. Multiple unanticipated predictions of the model were also verified experimentally. This research is presented in chapter 4 as a manuscript that will be submitted shortly. The final research stream of this thesis investigates forces in emulsions as they relate to a transition from glassy to crystalline dynamics. Specifically, 2D aggregates of droplets were compressed with micropipettes, providing both imaging of cluster evolution, as well as the force applied during compression. This research stream has demonstrated qualitative differences between droplet clusters that differ in composition so as to behave like crystals, glasses, or intermediate states. More quantitative analysis is required before this research stream is ready to be published. Preliminary results are presented in chapter 5.
Keywords: emulsion; droplet production; order; disorder; micropipette deflection; force measurement